Functional organization of vestibulospinal inputs responsible for tail postural control in larval Xenopus - Barrios, Gabriel; Olechowski-Bessaguet, Anne; Pain, Mathilde; Bacqué-Cazenave, Julien; Cardoit, Laura; Cabirol, Marie-Jeanne; Le Ray, Didier; Lambert, François M. (Frontiers in Neurology, 2024)
In all vertebrates, maintaining trunk posture primarily depends on descending commands originating from brainstem vestibulospinal nuclei. Despite being broadly outlined across species, the detailed anatomical and operational structure of these vestibulospinal networks remains poorly understood. Xenopus frogs have previously served as an excellent model for exploring such anatomical and functional aspects in relation to the animal’s behavioral requirements. In this study, we examined the reflex motor reactions induced by vestibular stimulation in pre-metamorphic tadpoles. Our findings indicate that natural vestibular stimulation in the horizontal plane yields greater efficacy compared to stimulation in other planes, a phenomenon replicated in a frequency-dependent manner through specific galvanic stimulation (GVS) of the horizontal semicircular canals. With the exception of a very rostral cluster of neurons that receive vestibular inputs and project to the spinal cord, the overall anatomical segregation of vestibulospinal nuclei in the brainstem mirrors that observed in juvenile frogs. However, our results suggest closer similarities to mammalian organization than previously acknowledged. Moreover, we demonstrated that vestibulospinal cells project not only to spinal motoneurons in rostral segments but also to more distal segments that undergo regression during metamorphosis. Lastly, we illustrated how vestibular-induced spinal reflexes change during larval development, transitioning from tail swim-based activity to rostral trunk bursting responses, likely anticipating postural control in post-metamorphic frogs.